The 2011 Tohoku Tsunami observed by an array of ocean bottom electromagnetometers. Issue 14 (23rd July 2014) - Zhang, Luolei; Baba, Kiyoshi; Liang, Pengfei; Shimizu, Hisayoshi; Utada, Hisashi
Abstract A tsunami induces secondary electromagnetic (EM) fields of significant intensity as a result of Faraday's law, and these EM fields can be recorded by instruments on the seafloor. Such observations will provide parameters that are useful in understanding tsunami generation and propagation processes. As such, EM sensors can be used as a type of tsunami sensor. In the present study, we report the observation of tsunami‐induced EM signals by a small array of ocean bottom electromagnetometers consisting of four stations in the northwestern Pacific Ocean. Then, several data analysis methods are used to estimate tsunami parameters. Referring to the theoretical relation, the wave height is estimated from the observed magnetic and electric fields. Also, the propagation direction of the 2011 Tohoku Tsunami is estimated by applying analysis methods for an array and a single station.